Recurrent Choking in a 40 days Old Infant: A Diagnostic Challenge - Ghosh, Uzzal Kumar; Sultana, Azmeri; Ferdoucy, Sultana Amena; Hossain, Md Delwar; Hasan, Md Samiul (Bangladesh Journal of Child Health, 2021)
Malrotation of the gut is a surgical problem. Clinical presentation is asymptomatic to symptomatic likes vomiting, abdominal distension, constipation, or sub-acute or acute intestinal obstruction. Rotational anomalies occur due to the arrest of normal rotation of the embryonic gut. Intestinal malrotation occurs when the normal embryological process of bowel rotation happens incorrectly or incompletely. Malrotation of gut was diagnosed by clinical features plus contrast radiograph and/or laparotomy. Our patient 40 days old infant presented with recurrent choking attack after breastfeeding with fever, cough, and respiratory distress. Infant was treated a case of aspiration pneumonia with gastroesophageal reflux, with keeping in mind trachea esophageal fistula and achalasia cardia like rare entity after exclusion of common etiology of choking. Pneumonia improved by treatment but choking persisted. Finally it was diagnosed as a case of partial malrotation of upper gut per-operatively. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 51-54